REPRESENTASI IDENTITAS LOMBOK DALAM AKUN INSTAGRAM “INSIDE LOMBOK”: ANALISIS SEMIOTIKA ROLAND BARTHES - Nurhandini, Hilmi; Firmonasari, Aprillia (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2024)
Social media is the factor that influences different perspectives about Lombok's identity. This research aims to describe the meaning of images that represent Lombok's identity in the Instagram account “Inside Lombok” using Roland Barthes' semiotic theory. The method used in this research is a qualitative method with descriptive analysis. The analysis in this study uses Roland Barthes's theory, including denotative meaning, connotative meaning, and myth. ““Inside Lombok”'s” post is the source of this research regarding the outsider's perspective on Lombok identity and the perspective of Lombok people regarding Lombok's identity itself. The results of the study show that the representation of Lombok's identity depends on how people perceive Lombok. According to the three images, there are hidden meanings that only Lombok people can discover. Therefore, the representation in social media should be clear so that everyone has a similar viewpoint.